Enhancing Professional Fluency: Leveraging Discourse Markers and Fluencemes in Vocational English Presentations - Aprillianti, Linda; Wulandari, Astri; Alif, Wening Nur Habibah; Adhelia, Shafira; Wardati, Rifka Uzma (Journal of English Language and Education, 2026)
Oral fluency is a vital competency for Business Administration students in global settings. However, the synergy between discourse markers (DMs) and fluencemes in vocational assessments remains under-researched. This qualitative study explicitly addresses: (1) what types of DMs and fluencemes appear in students' presentations; (2) what functional purposes these markers serve; and (3) how they influence message clarity and coherence. Analyzing nine speech transcripts from Semarang State Polytechnic via Crible’s (2018) DisFrEn framework , findings reveal that DMs and fluencemes act as strategic cognitive resources rather than mere errors. Students employ tactics like "Structural Anchoring" to maintain coherence under high cognitive load. Most participants fall into the "Effortful but Communicative" category. Consequently, vocational curricula should prioritize oral discourse management strategies over native-like accuracy to foster professional pragmatic competence in workplace communication